Modern control scheme for Z-Source inverter based PV power generation systems - Palanikumar, S; R, Selvakumar; Sivakannan, S (International Journal of Engineering and Technology, 2017)
Z-source inverter (ZSI) based photovoltaic power conversion system (PV-PCS) provides both the DC link voltage boost and DC-AC inversion in single stage with added features. Traditional maximum power point tracking (MPPT) control algorithm generates the required shoot-through interval to output maximum power to the Z-network. At this instant, the voltage across Z-source capacitor is equal to the MPP voltage of PV array. The capacitor voltage cannot be further increased if it is demanded by the load. This paper presents an improved MPPT control algorithm along with modified MPPT algorithm to achieve both the MPPT as well as capacitor voltage control at the same time. Development and implementation of the proposed algorithm has been carried out by Matlab/Simulink software and the results are provided.Â